Mapping the research landscape of energy market and renewable energy : A bibliometric analysis - Abdul Hayy Haziq, Mohamad; Rossazana, Ab Rahim (Centre of Biomass and Renewable Energy (CBIORE), 2025)
This bibliometric analysis examines the research landscape of "Renewable Energy" and "Energy Markets" from 2000 to 2023, with a specific focus on emerging trends during 2023 to 2024. The novelty of this study lies in its integration of bibliometric tools to analyse keywords, global contributions, thematic evolution, and future research directions. Using data extracted from Scopus and Web of Science (WoS), the study employs advanced bibliometric techniques, including keyword and term co-occurrence mapping through VosViewer. The findings reveal significant growth in research output in recent years, with 29 percent of Scopus and 44 percent of Web of Science publications produced during 2023 to 2024. China and the United States lead global contributions, while Malaysia and India exhibit rapid growth, each contributing more than 70 percent of their research in this period. Keyword analysis shows blockchain technologies, microgrids, and peer-to-peer energy trading as dominant themes, reflecting the rise of decentralised and digital energy systems. Thematic clusters underscore the convergence of technological innovation, policy frameworks, economic modelling, and regional strategies. Co-authorship networks reveal active collaboration across Asia-Pacific and European countries. Journal articles are the primary output type, with early-access publications highlighting the urgency of disseminating new findings. This study provides a comprehensive and up-to-date overview of the evolving discourse in renewable energy and energy markets. It offers actionable insights for researchers and policymakers while identifying underexplored areas that merit further investigation. The results support interdisciplinary approaches to addressing global energy challenges and advancing sustainable energy transitions.